Ultrafast, miniature soft actuators. Issue 4 (1st November 2021) - Bas, Onur; Gorissen, Benjamin; Luposchainsky, Simon; Shabab, Tara; Bertoldi, Katia; Hutmacher, Dietmar W
Abstract: The quest for an advanced soft robotic actuator technology that is fast and can execute a wide range of application-specific tasks at multiple length scales is still ongoing. Here, we demonstrate a new design and manufacturing strategy that leads to high-speed inflatable actuators exhibiting diverse movements. Our approach leverages the concept of miniaturisation to reduce the required volume of fluid for actuation as well as fibre-reinforcement to improve the efficiency of actuators in converting delivered fluids into fast and predictable movement. To fabricate the designs, we employ a class of additive manufacturing technology called melt electrowriting. We demonstrate 3D printing of microfibre architectures on soft elastomers with precision at unprecedently small length scales, leading to miniaturised composite actuators with highly controlled deformation characteristics. We show that owing to their small dimensions and deterministically designed fibrous networks, our actuators require extremely low amounts of fluid to inflate. We demonstrate that actuators with a length of 10–15 mm and an inner diameter 1 mm can reach their full range of motion within ∼20 ms without exploiting snapping instabilities or material non-linearities. We display the speed of our actuators by building an ultrafast, soft flycatcher. We also show that our actuators outperform their counterparts with respect to achievable movement diversity and complexity.